Social Return on Investment (SROI) from the Community Waste Bank Implementation under the Learning Center of Systematic Waste Management Innovation According to the Circular Economy Concept - Sridan, Pornpod; Surapolchai, Pichaya; Plainlaor, Thidasil; Tanyaim, Apinya; Hounnaklang, Nuchanad; Zongram, Onuma; Hawangchu, Yotwadee (Applied Environmental Research, 2024)
This article presents the results of social return on investment (SROI) evaluation in the community’s waste bank program implemented in the Moo 7 and Moo 8 Villages of Tan Diao Subdistrict, Kaeng Khoi District, Saraburi Province during 2020–2022, which is a part of the Learning Centre of Systematic Waste Management Innovation According to the Concept of Circular Economy project. This research employed participatory action research to collect data on total cost for investment and income from selling recyclable waste through in-depth interviews and focus groups with a total of 40 stakeholders including: 25 community members, 5 community leaders, 3 representatives from Tan Diao Subdistrict Administrative Organization, 5 village health volunteers, and 2 private waste buyers. The SROI analysis of the Moo 7 and Moo 8 waste banks (2020–2022) by using the discount rate based on the government bond yield at 3% shows the total net present value at 106,166.60 Thai Baht (2,941.76 USD), a ratio of cost-benefit analysis at 12.74 times, the payback period at 4.7 months, and the SROI result is 2.65 Thai Baht (0.073 USD). In other words, for every 1 Thai Baht invested in the community waste banks during this period, the benefits generated were equivalent to 2.65 Thai Baht (0.073 USD). This translates to a positive return on investment. The contribution of community waste bank under the project, can significantly change in 1) community relations with an intensive engagement in community waste management, 2) economic perspective as it generates employment and income, and reduces transportation costs for landfilling, and 3) environment term, as it reduces household waste and waste disposal. The suggestions have been developed in terms of policies and action plans for community waste management together with local administrative organizations to develop Tan Diao Subdistrict as a model of waste management.